2013
DOI: 10.1186/1476-4598-12-163
|View full text |Cite
|
Sign up to set email alerts
|

Microrna-124 targets flotillin-1 to regulate proliferation and migration in breast cancer

Abstract: BackgroundMicroRNAs (miRNAs) have been documented as playing important roles in cancer development. In this study, we investigated the role of miR-124 in breast cancer and clarified the regulation of flotillin-1 (FLOT1) by miR-124.MethodsThe expression levels of miR-124 were examined in breast cancer cell lines and patient specimens using quantitative reverse transcription-PCR. The clinicopathological significance of the resultant data was later analyzed. Next, we explored the function of miR-124 to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
102
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 45 publications
2
102
1
Order By: Relevance
“…Alteration of the expressions of miR-124 and miR-141 with their overexpressed plasmids and antisenses abolished the damage to hypoxia-induced vascular contractile response. This finding provides a new basis on which to treat hypoxia or shock-induced vascular hyporeactivity, the key complication of many critical illnesses such severe trauma, shock, sepsis, multiple organ dysfunction syndrome, and others (11,12). Nevertheless, whether other miRNAs that changed after hypoxia are involved in the regulation of hypoxia-induced vascular contractile dysfunction needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of the expressions of miR-124 and miR-141 with their overexpressed plasmids and antisenses abolished the damage to hypoxia-induced vascular contractile response. This finding provides a new basis on which to treat hypoxia or shock-induced vascular hyporeactivity, the key complication of many critical illnesses such severe trauma, shock, sepsis, multiple organ dysfunction syndrome, and others (11,12). Nevertheless, whether other miRNAs that changed after hypoxia are involved in the regulation of hypoxia-induced vascular contractile dysfunction needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported to function as an important regulator of many human cancers (43,44). In particular, recent studies have indicated that miR-124 targets specific genes to regulate proliferation and migration in breast cancer (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the genomic region containing the flotillin 2 gene is amplified in breast cancer tumors (Berger et al, 2013). Flotillin upregulation is detected in several types of cancers and it is associated with poor patient survival prognosis and high risk of metastasis formation (Doherty et al, 2006;Hazarika et al, 2004;Li et al, 2013;Pust et al, 2013;Rickman et al, 2008;Wang et al, 2013;Zhang et al, 2013;Zhu et al, 2013). In vivo analysis of the role of flotillins during tumorigenesis using a transgenic mouse model of breast cancer has shown that flotillin 2 is not involved in primary tumor formation, but is an important regulator of mammary-tumorderived lung metastasis (Berger et al, 2013).…”
Section: Disease Relevance Of Flotillin-mediated Roles At Adhesionsmentioning
confidence: 99%